Efektivitas Penggunaan Sistem CAT dalam Penerimaan Pegawai Negeri Sipil di UPT BKN Padang - Maharani, Ade; Adibarata, Risky Habib; Anggara, Tosa; Hanoselina, Yulia (PT Maju Malaqbi Makkarana, 2024)
The purpose of this study was to evaluate the effectiveness of the use of the Computer Assisted Test (CAT) System in the recruitment of Civil Servants (PNS) at the UPT BKN Padang. The CAT system is implemented to improve transparency, objectivity, and accountability in the recruitment of prospective civil servants. The research method used is qualitative with a descriptive approach, data collection is carried out through interviews, documentation, and literature reviews. The results of the study indicate that the implementation of the CAT system provides several benefits, including reducing time and costs, as well as improving the quality of test results. In addition, this system also helps reduce fraudulent practices and increases public trust in the recruitment process. Thus, the use of the CAT system is expected to be an effective solution in improving the quality of human resources for state apparatus in Indonesia. This study recommends the need for continuous evaluation of the CAT system to ensure sustainability and improvement in the recruitment process in the future.